Variable model for mechanical parameters of soft rock and elastoplastic solutions for tunnels considering the influence of confining pressure - Dong, Yucang; Zhang, Hai; Wang, Mingnian; Yu, Li; Zhu, Yongquan (Frontiers in Earth Science, 2023)
Accurate understating of influence of confining pressure on mechanical characteristics for soft rock, and how to comprehensively consider this influence in elastoplastic analysis for tunnel are the fundamental premise for the effective deformation control and stability evaluation of soft rock tunnel. Therefore, this paper firstly investigated the confining pressure effect on deformation and strength characteristic for phyllite and slate with triaxial experimental results and proposed variable models for mechanical parameter (E, v, c, φ) of soft rock with confining pressure variation. Secondly, according to the second stress state around tunnel and these variable models for mechanical parameter of soft rock, a new elastoplastic solution for tunnel was derived, which can simultaneously consider the confining pressure effect on deformation and strength characteristic of surrounding rock. Finally, by the proposed elastoplastic solution, the effect of multiple factors (initial pressure, supporting force and tunnel radius) on stress and displacement of surrounding rock around tunnel were analyzed.